(untitled) (American Journal of Islam and Society, 1998)
The Crown and the Turban is a new, valuable, and controversial contribution to two debates. First, it is a part of the debate on Africa’s triple heritage: African tradition, Islam, and Christianity. Second, it contributes to the debate on "secular" versus "religious" governance. For the first debate, the author argues that Muslims in West Africa are part of two encounters. First, they encounter the indigenous people and societies and particularly their traditional religions and political institutions. Second, they encounter Europeans who colonized and still indirectJy dominate West Africa. The reason for tension, the author claims, is what he calls "Islamic politicalism" and Muslim militancy on one hand and African tolerance and European secularism on the other. However, African Muslims are in an advantaged position compared to African Christians. African Muslims are indigenous and Islam is considered an African religion. Moreover, African Muslims demonstrate a political confidence based on an authentic tradition and long experience of Muslim rule in precolonial West Africa (p. 1). Nevertheless, the author argues that Africa offers a fresh opportunity to the adherents of the two missionary faiths, i.e., Islam and Christianity, vis-his the pluralist challenge of indigenous societies. Muslim and Christian Africans are already favored relatives in the African household but without the prodigal right or presumption to dispossess it or each other (p. 181). For the second debate, the author argues that Africa offers the promise, and the attendant hazards, of formulating and resolving the most crucial of debates for religious modernization: the debate on secular versus religious governance (p. 182). In the fmal analysis, the author approves and defends the secular governance as opposed to the religious one ...